Impact of new fire support capabilities from a joint functions perspective - Adrian MIREA (Bulletin of "Carol I" National Defense University)
The article highlights the usefulness of the operational framework described by the joint functions to understand the impact that an available capability has on the operation from an actional point of view. At the same time, this framework can also be exploited for the purpose of identifying a need for capabilities at the level of the current joint force in order to be able to accomplish the assigned missions. In order to argue the above, I have focused on a fire support capability that has recently become part of the national armed forces structures - the M142 HIMARS (High Mobility Artillery Rocket System). If in the first part of the article I briefly detailed aspects of the operational framework described by the joint functions, in the second part I presented a reasoned perspective on the impact that the capabilities of HIMARS systems have on the way of conceptualizing operations. The article aims to argue, through a concrete example, the possibility of using the operational framework described by the joint functions to understand the full potential of an existing or prospective capability for national armed forces structures.